Human Resources Factors and Management of Health Products and Technologies: A Multi-County Study on Access to Quality, Affordable Health Products and Technologies - Meme, Shadrack Mururu; Kawila, Carol; Njoroge, Kezia (International Journal of Professional Practice, 2026)
Health Products and Technologies (HPTs) are fundamental to realizing Kenya's Universal Health Coverage (UHC) goals, which emphasize high-quality medical services and minimized financial barriers. Despite efforts to improve HPT management, several counties face inefficiencies that hinder the consistent availability of affordable essential HPTs, undermining equitable access. This study investigated the impact of human resource for health (HRM) factors on the management of HPTs in selected Kenyan counties. Guided by management theory and the pragmatism paradigm, the research employed a mixed-methods design, using a descriptive survey for quantitative data and an exploratory approach for qualitative data. A census sampling technique encompassed 141 personnel responsible for HPT management at level 4 and 5 public health facilities, supplemented by key informant interviews with County Health Management Teams. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data underwent thematic analysis. The research revealed a correlation between human resource factors and HPT management of r = .509 (n = 106, P = .000). Human resource factors stood out as the most impactful predictor of HPT management (β = 0.251; t = 3.213; P = .002). Improving human resources for health enhances the availability of quality, affordable HPTs, advancing UHC. The study recommends a multidisciplinary Health Products and Technologies management Units (HPTUs) approach to foster collaboration among pharmacy, nursing, and clinical laboratory professionals for integrated, comprehensive HPT management.